Educational guidelines for eating “fill my plate” for balanced nutrition in toddlers - Marina, Marina (CV. Paperhome Indonesia, 2024)
High-quality human resources (HR) are essential for organizations, including in managing balanced nutrition for young children. Nutrition education, specifically through the